Practical application of high resolution ground penetrating radar method inside buildings - Mazurek, Ewelina; Łyskowski, Mikołaj (Geology, Geophysics and Environment, 2012)
An infrastructure development requires a precise indoor localization plan of cables, pipes or reinforcing elements. Due to the age of many buildings in Poland such plans often do not exist or do not contain the evidence of numerous activities carried out over years like repairs or modifications. Due to this situation demands for application of geophysical methods grow, especially with respect to the Ground Penetrating Radar (GPR) method. A possibility of precise localization of hidden objects arises with the use of high frequency antennas together and with precise measuring grid. Research carried out at the request of one of the departments of AGH University of Science and Technology in building B2 showed great potential of GPR methods in this field. The study was devoted to recognition of structure of the concrete floor. The obtained results gave very precise location of numerous objects of interest and they became a good sample of high resolution investigations. The survey was performed with ProEx unit, produced by a Swedish company - Mala Geoscience, which is in the possession of the Department of Geophysics, Faculty of Geology, Geophysics and Environmental Protection.